MEMPREDIKSI POLA DATA INDEKS HARGA SAHAM GABUNGAN DAN VOLUME PERDAGANGAN HARIAN DI BURSA EFEK JAKARTA PERIODE JANUARI JUNI TAHUN 2006 - -, Noeryanti (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
The choice of prediction in time series sequence, which produced valid and acurate prediction value is the main problem in prediction method. The study of data used by researcher was taken form website of Jakarta Stock Exchange (JSX) on menu of trade data addressed at http://www.jsx.co.id. Significant indikator in Stock Exchange Movement were IHSG and Trade Volume. Index functioned as market trend indicator, so from the index number, we know trend of stock volume movement today and extrapolate in the future. The aions of this research were to predict data pattern of IHSG and trade volume by using smoothing model approach since the best estimstion choice just compared some values of MSE, MAD, MSD and value. The result of analys shows that smooth mode of linear trend is very suitable for both datum. They are for IHSG and for Trade Volume. And then Box-Jenkins mode can be formed for IHSG data is ARIMA(1,0,0) and ARIMA(1,0,1) where as for Trade Volume data is ARIMA(0,0,1), ARIMA(1,0,0) and ARIMA(1,0,1).